Clinical and laboratory phenotypes in juvenile-onset Systemic Lupus Erythematosus across ethnicities in the UK. (April 2021) - Massias, Joseph S; Smith, Eve MD; Al-Abadi, Eslam; Armon, Kate; Bailey, Kathryn; Ciurtin, Coziana; Davidson, Joyce; Gardner-Medwin, Janet; Haslam, Kirsty; Hawley, Dan P; Leahy, Alice; Leone, Valentina; et al.
Systemic lupus erythematosus (SLE) is a systemic autoimmune/inflammatory disease. Patients diagnosed with juvenile-onset SLE (jSLE), when compared to individuals with adult-onset SLE, develop more severe organ involvement, increased disease activity and greater tissue and organ damage. In adult-onset SLE, clinical characteristics, pathomechanisms, disease progression and outcomes do not only vary between individuals and age groups, but also ethnicities. However, in children and young people, the influence of ethnicity on disease onset, phenotype and outcome has not been investigated in detail. In this study, we investigated clinical and laboratory characteristics in pediatric SLE patients from different ethnic backgrounds (White Caucasian, Asian, Black African/Caribbean) accessing data from a national cohort of jSLE patients (the UK JSLE Cohort Study). Among jSLE patients in the UK, ethnicity affects both the disease's clinical course and outcomes. At diagnosis, Black African/Caribbean jSLE patients show more "classical" laboratory and clinical features when compared to White Caucasian or Asian patients. Black African/Caribbean jSLE patients exhibit more renal involvement and more frequently receive cyclophosphamide and rituximab. Studies targeting ethnicity-specific contributors to disease expression and phenotypes are necessary to improve our pathophysiological understanding, diagnosis and treatment of jSLE.